Motivation to learn physical education through face-to-face learning in the COVID-19 pandemic - Luh Susiantari Pratiwi; I Wayan Artanayasa; I Made Satyawan (Universitas Sriwijaya, 2023)
This study aims to determine the motivation to learn physical education, sport,s and health through face-to-face learning during the COVID-19 pandemic for students at SD Negeri 2 Guwang in the 2021/2022 academic year. The type of this research is descriptive quantitative research with the h survey method. The population used in this study were students of SD Negeri 2 Guwang for the academic year 2021/2022, totaling 133 students ts. sampling technique used was a random sampling of as much as 25% of the total population of 33 students. The data collection technique used a closed questionnaire/questionnaire in several papers. Data were analyzed using quantitative descriptive statistics with percentages. The results of data analysis on motivation to learn physical education, sport, and health through face-to-face learning during the COVID-19 pandemic for students at SD Negeri 2 Guwang in the 2021/2022 academic year, as many as 19 students, or 57.575% have very high motivation, 14 participants students or 42.425% have high motivation, 0 students or 0% have moderate motivation, 0 students or 0.00% have low motivation, and 0 students or 0.00%. Based on the analysis of the data from the discussion, it can be concluded that the motivation to learn physical education, sport,s and health through face-to-face learning during the COVID-19 pandemic for students at SD Negeri 2 Guwang in the 2021/2022 academic year shows an average score of 66.3 with a very high category.